Natural Products as a Novel Therapeutic Strategy for NLRP3 Inflammasome-Mediated Gout - Lee, Jun Ho; Kim, Hyuk Soon; Lee, Jun-Ho; Yang, Gabsik; Kim, Hong Jun (Frontiers in Pharmacology, 2022)
Gout is the most common form of inflammatory arthritis. It occurs when monosodium urate crystals (MSU) are deposited within joints due to hyperuricemia and persistent elevations of serum uric acid levels. Traditional gout treatment such as urate-lowering therapy is difficult to continue for a long period of time due to the risk of side effects. Recent studies have shown that the modulation of MSU-induced inflammatory responses is dependent on the inflammatory cytokine IL-1β, which has a central role in a chain of processes involving multiple cytokines and mediators. In this regard, the NLRP3 inflammasome is known to play a crucial part and thus has been proposed as a novel target in the treatment for gout. However, the biochemical mechanism for NLRP3 inflammasome activation has not yet been clearly elucidated. Therefore, this report can provide an overview of natural extractions targeted to prevent or treat NLRP3 inflammasome-mediated gout in the MSU-induced gout model. In addition, the research and development of such natural products are suggested as a potential strategy in the treatment of gout.